Integrated Approaches for Managing Bacterial Wilt Disease (Enterobacter sp.) in Aceh Patchouli Plants - Sriwati, Rina; Khairan, Khairan; Hifnalisa, Hifnalisa; Fikrinda, Fikrinda; Oktarina, Hartati; Zulfadli, Zulfadli; Wasistha, Nurainun Intan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Aceh Patchouli (Pogostemon cablin Benth.) is a significant export commodity for essential oil production in Indonesia. The wilt disease “matee tumbon” caused by Enterobacter bacteria is one of the obstacles to Aceh patchouli cultivation. This study aims to identify the most effective combination technique to control it. The study combined 25 treatment combinations in patchouli nurseries, and the five best treatment combinations were subsequently tested on patchouli plants in the field. The results showed that the five best combinations in controlling bacterial wilt disease in the nursery were 20% streptomycin sulfate + Trichoderma sp., 20% streptomycin sulfate + Bacillus thuringiensis, Trichoderma sp. + B. thuringiensis, 20% streptomycin sulfate + neem extract + B. thuringiensis, and neem extract + Trichoderma sp. + B. thuringiensis. Field results showed that the combination of neem extract, Trichoderma sp., and B. thuringiensis was effective in controlling the pathogen Enterobacter sp., causing bacterial wilt disease in Aceh patchouli plants. This combination of control techniques is an integrated approach to controlling bacterial wilt disease (Enterobacter sp.) in Aceh patchouli plants.